Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/21553769.2015.1089949
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activities of several plant extracts from Turkey on rat brain tumor and human cervix carcinoma cell lines

Abstract: Turkey has a wide range of flora and fauna due to its climatic diversity. Medicinal plants from Turkey have been used since ancient times for their primary health care. In this study, we examined antiproliferative activities of the extracts from Crataegus monogyna, Vitis vinifera, Glycrrhiza glabra, Alnus glutinosa L. gaertn, and Alcea rosea against rat brain tumor (C6) and human cervical cancer (HeLa) cell lines. The results were compared with the standard anticancer drugs 5-Flurouracil (5-FU) and Cisplatin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It was also found that these extracts did not show antimicrobial activity against Pseudomonas aeruginosa CMUL 241, Escherichia coli CMUL 577, Staphylococcus aureus CMUL 491, Candida albicans ATCC 10231 strains (32). In another study, it was found that methanol extract from Alcea rosea aerial parts showed strong and selective cytotoxic activity on HeLA (IC 50 : 14.48 µg/mL) cells and C6 cell lines (37.63 µg/mL) (33). As a result of the in vivo experiment of water extract from flowers of Alcea aucheri, this extract has been disclosed to have strong anxiolytic and sedative properties (34).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that these extracts did not show antimicrobial activity against Pseudomonas aeruginosa CMUL 241, Escherichia coli CMUL 577, Staphylococcus aureus CMUL 491, Candida albicans ATCC 10231 strains (32). In another study, it was found that methanol extract from Alcea rosea aerial parts showed strong and selective cytotoxic activity on HeLA (IC 50 : 14.48 µg/mL) cells and C6 cell lines (37.63 µg/mL) (33). As a result of the in vivo experiment of water extract from flowers of Alcea aucheri, this extract has been disclosed to have strong anxiolytic and sedative properties (34).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the anticancer properties of natural extracts, recent studies showed that, natural extracts can be more effective therapeutic agents against tumors than standard chemotherapeutic candidates (118). It was demonstrated that the methanol extract of Crataegus monogyna (Rosaceae) exhibited better antiproliferative activity than standard chemotherapeutics 5-flurouracil and cisplatin on brain tumors and cervical cancer cells (119). Furthermore, the natural extracts can be added to the standard anticancer drugs for increasing their treatment effectiveness and reducing their side effects.…”
Section: Rosaceaementioning
confidence: 99%
“…This suggests that flavone compounds have a potential application in the prevention and treatment of cancer. Studies have investigated the cytotoxicity and antiproliferative activities of extracts obtained from various herbs ( 26 , 27 ). The in vitro cytotoxic effects of numerous herbal extracts have been investigated on MDA-MB-231 and MCF-7 breast cancer cells ( 28 ).…”
Section: Using Rtca Systems To Measure the Cytotoxicity Of Compounds mentioning
confidence: 99%